2015
DOI: 10.1177/0003319715607298
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Patients With Acute Decompensated Heart Failure

Abstract: We assessed sex-specific differences in clinical features and outcomes of patients with acute heart failure (AHF). The Heart function Assessment Registry Trial in Saudi Arabia (HEARTS), a prospective registry, enrolled 2609 patients with AHF (34.2% women) between 2009 and 2010. Women were older and more likely to have risk factors for atherosclerosis, history of heart failure (HF), and rheumatic heart and valve disease. Ischemic heart disease was the prime cause for HF in men and women but more so in men (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On discharge, men had a higher use of ACE-Is (62.8% vs. 53.4%; p < 0.001), beta-blockers (85.8% vs. 79.3%; p < 0.001), and aldosterone inhibitors (42.1% vs. 30.9%; p < 0.001) compared with women. Apart from higher atrial fibrillation (AF) in women (8.4% vs. 4.7% in men; p < 0.001) and higher ventricular arrhythmias in men (4.8% vs. 3% in women; p = 0.029), no differences were observed in hospital outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…On discharge, men had a higher use of ACE-Is (62.8% vs. 53.4%; p < 0.001), beta-blockers (85.8% vs. 79.3%; p < 0.001), and aldosterone inhibitors (42.1% vs. 30.9%; p < 0.001) compared with women. Apart from higher atrial fibrillation (AF) in women (8.4% vs. 4.7% in men; p < 0.001) and higher ventricular arrhythmias in men (4.8% vs. 3% in women; p = 0.029), no differences were observed in hospital outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Male gender was also an independent risk factor for all-cause mortality. A study conducted in Saudi Arabia found no significant difference in survival between women and men [ 12 ]. Our findings were reported in a recent UK study in which women had a 14% age‐adjusted lower risk of all‐cause mortality [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth to note that, like coronary artery disease and atrial fibrillation, RHD may have sex differences in etiology, presentation, co-morbidities, management and outcome[2023]. Previous studies have reported the sex-dependent difference in disease prevalence, risk factor, progression and therapeutic outcome in RHD[79]. However, no study has been dedicated to investigate a potential sex difference in aortic valve pathology in RHD.…”
Section: Discussionmentioning
confidence: 99%